The profile of homeless psychosocial care center users (Research, Society and Development, 2021)
Objectives: to know the sociodemographic profile of the homeless population with mental disorders attended at an adult CAPS in the western region of the city of São Paulo; to compare the results obtained in the present study with data from the census of the social development department of the Municipality of São Paulo; and analyze similarities and differences. Method: This quantitative, cross-sectional study. Result: male individuals, black, from the state of São Paulo, with an average age of 42.83 years, single, with low education, unemployed, without income, has been hospitalized in a psychiatric hospital for more than a year, make use of tobacco and who live in shelter. Most have already suffered some type of violence and discrimination in the street. The prevalent diagnoses were common mental disorders. The data from the present study are similar to data found in the municipal census of homeless people in the municipality. Conclusion: thanks to the public mental health policy, homeless people with mental disorders have more access to shelter when compared to homeless people without mental disorders. However, the other axes, such as work and social network, still need more strategies towards social inclusion. It appears that the stigma of mental disorders, in addition to marginality, racism and unemployment, further aggravates society's imagination in relation to these people. Thus, the need for more intersectoral actions is suggested in order to meet the demands of this specific population and to combat the stigma of mental disorders.